PENGARUH GOOD CORPORATE GOVERNANCE DAN INTELLECTUAL CAPITAL TERHADAP FINANCIAL PERFORMANCE (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia) - Indriyani Ningsih Sinurat; Sylvia Christina Daat; Linda Y. Hutadjulu (JURNAL AKUNTANSI DAN KEUANGAN DAERAH, 2019)
This study aims to examine the influence of good corporate governance and intellectual capital to financial performance (financial performance). Corporate governance mechanisms in this research are managerial ownership, institutional ownership, and the proportion of independentcommissioners. Intellectual capital is measured using Value Added Intellectual Capital (VAIC) model which has three components (physical capital, human capital and structural capital), and financial performance is measured by return on assets (ROA). Secondary data was used by derived from the financial statements of manufacturing companies listed on the Indonesia Stock Exchange 2014-2016. The sampling technique used purposive sampling method with multiple linear regression analysis tools. Prior the regression test, the classical assumption test is done first. The results show that managerial ownership, institutional ownership and independent commissioner's proportion have no effect on financial performance, while intellectual capital has an effect on financial performance. The conclusion of this research is that intellectual capital can be used to improve financial performance if company can measure accurately but corporate governance still not proven can improve company's financial performance.